2019
DOI: 10.1002/pd.5477
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcomes of ex‐utero intrapartum treatment (EXIT)

Abstract: Background/Purpose: The ex-utero intrapartum treatment (EXIT) procedure is used to secure effective gas exchange prior to postnatal life. We describe the obstetrical course and maternal outcomes of a series of patients who underwent EXIT.Methods: This is a review of all pregnancies in which fetuses were delivered by EXIT from January 2001 to April 2018. Outcome variables included estimated gestational age (EGA) at delivery, need for emergency EXIT, maternal estimated blood loss (EBL), need for maternal blood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
1
14
0
2
Order By: Relevance
“…Obstetric outcomes in this retrospective study are comparable to previous evaluations of EXIT for cervical teratomas. Length of hospital stay was similar to that reported in previous studies 14 15 There were quite some patients with polyhydramnios who required amnioreduction, and most had subsequent preterm contractions.…”
Section: Discussionsupporting
confidence: 84%
“…Obstetric outcomes in this retrospective study are comparable to previous evaluations of EXIT for cervical teratomas. Length of hospital stay was similar to that reported in previous studies 14 15 There were quite some patients with polyhydramnios who required amnioreduction, and most had subsequent preterm contractions.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, 3/65 patients had a placental abruption 26 . Finally, another single‐center study reviewed EXIT procedures and found 6/45 (13%) patients required a maternal blood transfusion 27 . The potential need for transfusion is undoubtedly higher in EXIT procedures, as additional blood loss can occur if uterine tone does not increase following delivery.…”
Section: Error Trap 4: Failure To Adequately Prepare For Maternal Hemmentioning
confidence: 99%
“…En una serie de 45 casos, donde 35,6% fueron de emergencia, fue reportada una pérdida hemática media de 800 mL (500-2.000), en las que un 13,3% de las pacientes recibieron transfusión. La estadía hospitalaria fue de unos 4 días (3-7) 1 .…”
Section: Enfrentamiento Del Caso Clínicounclassified
“…Fetos con potencial obstrucción de vía aérea neonatal, como los diagnosticados con masas cervicales congénitas, síndrome de obstrucción de vía aérea alta congénito (CHAOS por sus siglas en inglés) y micrognatia severa requieren de manejo especializado de la vía aérea al momento del parto 1 . Estas patologías han sido asociadas históricamente con pobres resultados, donde la asfixia y muerte perinatal eran frecuentes [2][3][4][5][6][7][8] .…”
Section: Introductionunclassified